Folkbiblioteket och marknaden - En diskursanalys av ideologiska konflikter i diskussionen om marknadsanpassning av folkbibliotek - Strandqvist,Ola (2007)
The recent decades have been characterised by a trend where the public sector's been inspired by several methods and strategies from the private sector. The public library is in this case no exception. In this context there are different perspectives on whether or not this will lead to a dramatic change of the role and values of the traditional public library. The aim of this master's thesis is to make a contribution to a deeper understanding of the ideological conflicts within the Swedish public library and its relation to the market. In the literature of library and information science I have identified two separate discourses representing two contradictory systems of meaning concerning this relation. The first I have identified as a discourse of marketization while the other is identified as a discourse of democracy. The main question asked in this study is how these two discourses tend to interact and how the conflict between them is expressed regarding the public library and the market. The analysis is based upon the discussion held in articles within Swedish library press during the years 2005 and 2006. The theoretical framework is based on Ernesto Laclau's and Chantal Mouffe's theory of discourse which is combined by Norman Fairclough's method and techniques of analysing discourses in text. The conclusion of the thesis is that both discourses appear in the articles as two competing semiotic systems of meaning. The discourse of marketization is based on liberalism and theories on market economy. The public library is placed in a context where its role for economic growth, education and for the satisfaction of individual market demands is central. The discourse of democracy is in contradiction based upon theories on participatory democracy and socialist terminology. The public library is in the discourse of democracy defined as an institution with the main purpose to intermediate values and meaning in the civil society. The most central role is to work for an equal distribution of power, knowledge and influence and further stimulate the democratic activities among the citizens. The interplay of the two discourses is characterised by a pattern showing that the discourse of marketization has a dominating position. This is based on a conclusion that the discourse of marketization and its system of meaning is legitimised by references to objectivity, universalism and common sense. This pattern is according to Laclau and Mouffe characteristic for a discourse heading towards hegemony. The discourse of democracy tends to challenge this situation by expressing its difference related to the ideology behind the discourse of marketization. However this seems to fail. My analysis reveals that ideological conflicts regarding the public library and its relation to the market do exist in some matters, but that the main conflict rather concerns whether or not this relation should be placed in an ideological dimension at all. The dominant position of the discourse of marketization is contributing to a restrainment of ideological perspectives. I consider this to be a problem. By not discussing ideological values, the public library might loose its awareness of how it can and should make impact on society regarding social issues such as democracy, equal distribution of knowledge and power etc.
Keywords: diskursanalys; folkbibliotek; ideologi; marknad; demokrati; konflikt; Documentation, information, library science, archivistics; Arkiv- och bibliotekskunskap, dokumentation